Big Tree - Selznick, Brian (New York : Scholastic Press, 2023)
"Sycamore seed siblings Merwin and Louise must use their wits and imaginations to navigate a mysterious and often dangerous world, filled with talking plants, monsters, meteors, and the fear of never finding the right conditions to set down roots and become big trees"--
Keywords: Seeds -- Juvenile fiction; Sycamores -- Juvenile fiction; Trees -- Juvenile fiction; Paleontology -- Juvenile fiction; Seeds -- Fiction; Trees -- Fiction; Paleontology -- Fiction; Juvenile Fiction; Novels